2014
DOI: 10.1179/1743284713y.0000000485
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of Al rich Fe–Mn–Al–C low density steels

Abstract: The surface quality of steels containing solutes that have a strong affinity for oxygen can be markedly compromised during processing at elevated temperatures. Here, we examine a class of steels that are being developed for low density applications and hence, have relatively large concentrations of aluminium and manganese. These two elements compete for what little oxygen is available in the predominantly hydrogen–nitrogen mixture used to protect the steel during heat treatment. It is found that although the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Steels with Mn content lower than 7.5 wt.% formed layers consisting of Al 2 O 3 and Fe-like oxides, while the oxide layer was highly enriched in Mn for steels with Mn content greater than 7.5 wt.% [15]. It was also found that the formation of Al 2 O 3 and Mn-rich oxides essentially compete with each other [16]. Grain size also plays a role, as grain refinement accelerates phase transformation and promotes the rapid formation of Al 2 O 3 layers and slightly improves oxidation resistance [17].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Steels with Mn content lower than 7.5 wt.% formed layers consisting of Al 2 O 3 and Fe-like oxides, while the oxide layer was highly enriched in Mn for steels with Mn content greater than 7.5 wt.% [15]. It was also found that the formation of Al 2 O 3 and Mn-rich oxides essentially compete with each other [16]. Grain size also plays a role, as grain refinement accelerates phase transformation and promotes the rapid formation of Al 2 O 3 layers and slightly improves oxidation resistance [17].…”
Section: Introductionmentioning
confidence: 90%
“…Studies have been carried out on the high-temperature oxidation behaviour of Fe-Mn-Al-C steels. It was found that the addition of Al promotes the formation of an Al 2 O 3 layer, which prevents further oxidation and has a high protective effect [13][14][15][16][17][18]. Furthermore, an increasing C content increases the weight gain per unit area and the thickness of the oxide layer formed, which leads to the deterioration of the high-temperature oxidation resistance [13].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The internal oxidation of alloying elements has been also an important subject with respect to the control of the continuous annealing condition, which is a reduction atmosphere to Fe. [9][10][11][12] However, the formation of alloy oxides in a high oxygen potential, in particular, the internal oxidation behaviour and the resultant concentration profile of alloying element beneath the external scale has rarely been investigated systematically. 13 In the present study, we examine the oxidation behaviour of Si-containing low-carbon steels in an atmospheric condition.…”
Section: Introductionmentioning
confidence: 99%